Tramadol-Induced Mood Elevation in a Patient with No Previous Psychiatric History - Osman, Mugtaba; Mustafa, Mashael (Case Reports in Psychiatry, 2018)
Tramadol is a powerful analgesic medication with antidepressant effects like venlafaxine. Hypomanic features were reported in patients with psychiatric history of mood disturbance when tramadol was prescribed for them. However, it is extremely rare to notice such mood-elevating effect in patients who have no previous psychiatric history. We report on the observation of a distressing mood-elevating effect for tramadol in a patient with no previous psychiatric history. We present the case of a 26-year-old female patient who developed accelerated flow of speech, overactivity, and difficulty in sleeping following intake of tramadol 50 mg dose. These symptoms resolved four hours later and recurred as she retook tramadol. The patient has no history of mood disorder or any other psychiatric comorbidity. Clinicians should exercise caution when prescribing tramadol.